Proyek food estate pada lahan eks pengembangan lahan gambut di Kalimantan Tengah: perlu atau tidak? - Izzati, Amrina Nur; Gustiawati, Beatriks Liku; Saputra, Rizal Yoga (Institute for Advanced Science Social, and Sustainable Future, 2023)
Food estate development is one of ten National Strategic Programs (PSN) for 2020-2024 carried out by the government to restore the economy due to the impact of the COVID-19 pandemic. The government, through the Minister of Public Works and Public Housing (PUPR), stated that the food estate project was carried out on a potential land area of 165,000 ha, which is an alluvial area, not peat, on former Peat Land Project (PLG) land in Central Kalimantan. PLG was a government policy during the New Order era, with the opening of one million hectares of PLG to address agricultural development's challenges to achieve self-sufficiency. In 1998, this program was discontinued because it was considered unsuccessful in its planning and implementation, which did not pay enough attention to environmental impacts. This study examines government policy in implementing the food estate program on former PLG land in Central Kalimantan. The study covers environmental and socio-economic aspects that are affected by the food estate program on former PLG land. The research method applies a qualitative approach by searching literature reviews on implementing food estate projects on former PLG land in Central Kalimantan. The results show that government policy through the Minister of Environment and Forestry Regulation Number 24 of 2020 regulates two schemes for providing forest areas for the food estate program, namely through schemes for changing the designation of forest areas and establishing forest areas for food security. Both schemes could accelerate environmental exploitation and deforestation in Central Kalimantan, which previously experienced failure in the Million Hectare PLG project. In the socio-economic aspect, food estate development must involve the surrounding community, and it is necessary to improve the quality of farmers, which includes 1) increasing knowledge, skills, and community assistance, 2) facilitating the opening of marketing networks, and 3) establishing institutions between stakeholders at the local and central levels. Implementing the food estate program in Indonesia requires an operational strategy using strong sustainability theory to minimize environmental, economic, and social impacts so that program failure does not occur as in previous policies.